The Influence of Brand Reputation and Price on the Decision to Purchase Counterfeited Crocs Products (Case Study of Users of Fake Crocs Products, South Jakarta) - Tampubolon, Irene Lily; Sofia, Evi (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this research is to examine: The Influence of Brand Reputation and Price on Purchase Decisions for Counterfeited Crocs Products (Case Study of Users of Fake Crocs Products in South Jakarta). This research used a sample of 100 samples, with the criteria being consumers who had used fake Crocs products and consumers who were still using fake Crocs products. The data analysis that researchers used in this research used descriptive analysis, data quality testing, classical assumption testing, multiple linear regression testing, hypothesis testing, and coefficient of determination testing. The software that researchers use is SPSS version 25. The results of this research are: 1) Based on the results of the T test, it is known that the sig value is 0.000 < 0.05, meaning that the Brand Reputation variable (X1) statistically has a positive and significant effect on Purchasing Decisions (Y).Â  2) Based on the results of the T Test on the Price variable, it is known that the sig value is 0.015 < 0.05, meaning that the Price variable (X2) statistically has a positive and significant effect on Purchasing Decisions (Y). 3) The Brand Reputation and Price variables simultaneously have a significant effect on Purchasing Decisions by having a sig value of 0.000 <0.005, meaning they have a positive and significant effect on Purchasing Decisions (Y) simultaneously.